Diversity and evolution of Bradyrhizobium communities relating to Soybean cultivation: A review. Issue 1 (June 2021) - Saranraj, P; Sivasakthivelan, P; Al-Tawaha, A R M; Sudha, A; Al-Tawaha, A R; Sirajuddin, S N; Hastang
Abstract: Soybean is a nitrogen fixer. Also it is a model plant for the study of biological nitrogen fixation (BNF). Soybeans produce more protein and vegetable oil per acre than they do. Over 5000 years, China has been the centre of global soybean production. The Chinese Academy of Agriculture Sciences (CAAS) institute for crop germplasm resources has a national gene bank called the National Gene Bank (NGB) that is made up of nearly 24, 000 soybean accessions, which include both wild and domesticated varieties. It started in the 18th century, but more intense cultivation started in the latter half of the 20th century. This has led to North America becoming the world's leading soybean producer. This present review is focused on the diversity and evolution of Bradyrhizobium communities relating to Soybean cultivation.